(3CSGfjO cJGH ef dG jMVQg Gdabjgs - (3Gdbej, GdTjN GdUOhb, GHf HGHhjg Gdbej, eMeO Hf Ydj Hf GdMSjf, J (B381(3g` (B991(3es ((3jYbhH Hf eMeO Ydj GdgRQGLQjHjs)
(3ChdgG (B:s
(3ChdgG(B: (3jbhd eMeO Hf Ydj Hf GdMSjf (B... (3cd eG cGf aj gPG GdcJGH Yf YeGQ Hf ehSi GdSGHGWj abO QhjJg Yf CHj heMeO Hf GdMSf Hf CMeO Hf GdhdjOs
(3BNQgG (B:s
(3BNQgG(B: (3heG cGf ajg Yf SYO Hf WQja GdNaGa abO QhjJg Yf CHj QVj Gddg Yfg Yf SYO Hf YHO Gddg Yf GdgjKe Hf CHj eSQhb GdfgOj Yf GdMSjf Hf YdhGf Yf YeQ Hf KGHJ Yf ShQ Hf WQja GdNaGa(B. (3JeJ CSGfjO cJGH ef dG jMVQg Gdabjgs
(3jdjgG agQS QLGd SfO cJGH ef dG jMVQg Gdabjg, hjdjgG fbhd eNJdaI ef (B477 - 484s
(3JHUQI GdYfhGf (B:s
(3PcQ aj GdPQjYI TQhM dgPG GdcJGH hde jPcQ faSgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 274s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs